Prospective randomized comparison of endoscopic submucosal tunnel dissection and conventional submucosal dissection in the resection of superficial esophageal/gastric lesions in a living porcine model - Gomercic, Cécile; Vanbiervliet, Geoffroy; Gonzalez, Jean-Michel; Saint-Paul, Marie-Christine; Garcès-Duran, Rodrigo; Garnier, Emmanuelle; Hébuterne, Xavier; Berdah, Stéphane; Barthet, Marc (Endoscopy International Open, 2015)
Background and study aims: To assess experimentally endoscopic submucosal tunnel dissection (ESTD) as an alternative technique of endoscopic submucosal resection.Patients and methods: This was a prospective, randomized, comparative experimental animal study carried out over a period of 9 months at the surgical research and teaching center of Aix-Marseille University, France. Virtual esophageal and gastric lesions measuring 3 cm in diameter were resected in pigs weighing 25 to 30 kg. The primary aim was to evaluate ESTD’s efficacy compared with endoscopic submucosal dissection (ESD). The secondary aims were to determine complication rates as well as to assess procedure time and procedure speed, histologic quality of the resected specimen, and procedure cost.Results: Eighteen procedures (9 ESD and 9 ESTD) were performed in nine pigs. The technical success rate was 88.9 % for both techniques, with one single failure in each. The en bloc resection rate was 100 % for ESTD and 88.9 % for ESD (one failure). The complication rate (22 %) and median procedure time were similar but dissection speed was quicker with ESTD in the esophagus (P = 0.03). Median procedure cost (728 Euros for ESD and ESTD) did not differ. On histologic examination, the lateral margins were healthy in 100 % of ESTD and in 88.9 % of ESD (P = 0.49). Deep resection margins were of better quality in ESTD (median submucosal thickness: 1307.1 µm vs. 884.7 µm; P = 0.039). Conclusions: ESTD is feasible and safe but not superior in the treatment of superficial esophageal/gastric lesions in porcine models compared with ESD. Nevertheless it provides a better quality histologic specimen.